Remote Piloting UAS in Extreme Environments with Challanging Climatic Conditions - An Overview of Modern UAS Capabilities in the Field of Volcanology, Geosciences, Atmospheric Chemistry and Interplanetary Exploration - Godfrey, Ian (2022)
Unmanned Aerial Systems have recently had advanced payloads configured by engineers for various atmospheric sampling experiments and have been proven a successful and innovative technology. Climatic stability in volcanic regions can change in less than one minute. And with that comes relative humidity fluctuations, 80% change in visibility conditions, wind speed change, wind direction change, enhancing wind gusts. Its the data collection on how UAS operate in these conditions that will eventually assist the development of UAS with the ability to conduct complex photogammetry and atmospheric sampling flight missions of the Moon and Mars. For this reason we created a short article on our findings on using UAS in some of the most extreme and complicated atmospheric enviroments.